Klippel–Trenaunay syndrome presenting as pulmonary embolism in an elderly person - P. K. Surendran; L. Asha Krishnan; C. M. Ali Sayyad; V. Udayabhaskaran (Journal of Clinical and Scientific Research)
An elderly woman was admitted with acute-onset breathlessness and right-sided chest pain suggestive of pleurisy. The initial impression of the chest X-ray was ‘right upper lobe consolidation’. Her hypertrophied leg along with the presence of large visible arteriovenous malformation was suggestive of Klippel–Trenaunay syndrome (KTS). A conscientious relook at the X-ray revealed other radiological features suggesting a possible pulmonary embolism. Subsequent D-dimer and echocardiography supported the diagnosis, and a computerised tomography pulmonary angiogram confirmed the same. Prompt systemic anticoagulation along with supportive therapy led to a smooth recovery of the patient over the next few days.